Self assembled CdLa2S4 hexagon flowers, nanoprisms and nanowires: novel photocatalysts for solar hydrogen production - Kale, Bharat B.; Baeg, Jin-Ook; Kong, Ki-jeong; Moon, Sang-Jin; Nikam, Latesh K.; Patil, Kashinath R. (Journal of Materials Chemistry, 2011)
We report here a new ternary chalcogenide material, cadmium lanthanum sulfide (CdLa2S4) produced using a facile hydrothermal method at 433 K. The effect of the solvent on the morphology of the CdLa2S4 was demonstrated for the first time. The prima facie observations revealed the formation of highly crystalline hexagonal structures in the form of flowers in aqueous medium. The flowers comprise hexagonal columns similar to 300 nm in diameter and 1-1.2 mu m in length. All the hexagonal structures have a sharp tip with a cavity of 10 nm and are almost equal in size. The nanoprisms have an average base size of 35 nm with 35 nm edges, and the nanowires have a diameter of 10-15 nm; both were obtained in methanol. Crystal and electronic structure calculations were performed using the Vienna ab initio simulation package (VASP) based on density functional theory (DFT). Considering the band gap of pristine CdLa2S4 in the visible region (2.3 eV), we have demonstrated CdLa2S4 as a photocatalyst for the production of H-2 under solar light. Nanostructured CdLa2S4 prisms gave the maximum hydrogen production, i.e. 2552 mu mol h(-1). Being a stable ternary nanostructured metal sulfide (with nanohexagons, nanoprisms, nanowires), CdLa2S4 may have other potential prospective applications in solar cells and optoelectronic devices.

Situ preparation of N-TiO2/graphene nanocomposite and its enhanced photocatalytic hydrogen production by H2S splitting under solar light - Bhirud, Ashwini P.; Sathaye, Shivaram D.; Waichal, Rupali P.; Ambekar, Jalindar D.; Park, Chan-J.; Kale, Bharat B. (Nanoscale, 2015)
Highly monodispersed nitrogen doped TiO2 nanoparticles were successfully deposited on graphene (N-TiO2/Gr) by a facile in-situ wet chemical method for the first time. N-TiO2/Gr has been further used for photocatalytic hydrogen production using a naturally occurring abundant source of energy i.e. solar light. The N-TiO2/Gr nanocomposite composition was optimized by varying the concentrations of dopant nitrogen and graphene (using various concentrations of graphene) for utmost hydrogen production. The structural, optical and morphological aspects of nanocomposites were studied using XRD, UV-DRS, Raman, XPS, FESEM, and TEM. The structural study of the nanocomposite shows existence of anatase N-TiO2. Further, the details of the components present in the composition were confirmed with Raman and XPS. The morphological study shows that very tiny, 7-10 nm sized, N-TiO2 nanoparticles are deposited on the graphene sheet. The optical study reveals a drastic change in absorption edge and consequent total absorption due to nitrogen doping and presence of graphene. Considering the extended absorption edge to the visible region, these nanocomposites were further used as a photocatalyst to transform hazardous H2S waste into eco-friendly hydrogen using solar light. The N-TiO2/Gr nanocomposite with 2% graphene exhibits enhanced photocatalytic stable hydrogen production i.e. similar to 5941 mu mol h(-1) under solar light irradiation using just 0.2 gm nanocomposite, which is much higher as compared to P25, undoped TiO2 and TiO2/Gr nanocomposite. The enhancement in the photocatalytic activity is attributed to `N' doping as well as high specific surface area and charge carrier ability of graphene. The recycling of the photocatalyst shows a good stability of the nanocomposites. This work may provide new insights to design other semiconductor deposited graphene novel nanocomposites as a visible light active photocatalyst.

Situ fabrication of highly crystalline CdS decorated Bi2S3 nanowires (nano-heterostructure) for visible light photocatalyst application - Panmand, Rajendra P.; Sethi, Yogesh A.; Deokar, Rajashree S.; Late, Dattatray J.; Gholap, Haribhau M.; Baeg, Jin-Ook; Kale, Bharat B. (RSC Advances, 2016)
In situ synthesis of the orthorhombic Bi2S3 nanowires decorated with hexagonal CdS nanoparticles (nano-heterostructure) has been demonstrated by a facile solvothermal method. The tiny 5-7 nm CdS spherical nanoparticles are decorated on the surfaces of 30-40 nm Bi2S3 nanowires, successfully. Structural, morphological and optical studies clearly show the existence of CdS on the nanowires. A possible sequential deposition growth mechanism is proposed on the basis of experimental results to reveal the formation of the nano heterostructure. The heterostructures have been used as a photocatalyst for hydrogen production as well as degradation of methylene blue under solar light. The maximum hydrogen evolution i.e. 4560 and 2340 mu mol h(-1) 0.5 g was obtained from H2S splitting and glycerol degradation for Bi2S3 NWs decorated with CdS nanoparticles (nano-heterostructure) which is higher than that of the Bi2S3 NWs (3000 and 1170 mu mol h(-1) 0.5 g, respectively). The enhanced photocatalytical hydrogen evolution efficiency of the heterostructures is mainly attributed to its nanostructure. In the nano heterostructure, the CdS nanoparticles control the charge carrier transition, recombination, and separation, while the Bi2S3 nanowire serves as a support for the CdS nanoparticles. The photogenerated electron's migration is faster than the holes from the inside of a CdS nanoparticle to its surface or to the phase interface, resulting in a relatively higher hole density inside the CdS nanoparticle leaving electron density at surface of the Bi2S3 NWs. This influences the photocatalytic activity under solar light. Such nano-heterostructures may have potential in other photocatalytic reactions.